Transition from face to face to virtuality in cooperative work activities In an inclusive theater workshop (Innovaciones Educativas, 2022)
The present systematization aims to analyze the transition of cooperative work in the Rompe Puzzle Theater Group, from face-to-face to virtual space, during the COVID-19 pandemic, in a theater workshop that aims to develop social skills in young people with disabilities. For this, a content analysis of the logs and videos of the work sessions in improvisation subgroups was carried out, in which 15 young people with disabilities participated, in addition to a survey of these and the people facilitating the space. It was found that the experience to adjust to virtuality, the type of activity that was already carried out in person, gave a more preponderant role to the facilitator to ensure the work dynamics of the subgroups. The technique consisted of subgroups and a basic premise to improvise together in the virtual session-whether a scene or a song, in person, or a joint story. A group structure of the informal type was used, making small groups randomly facilitating the role of the formal type, which guides the subgroups in cooperative work. Some of the components of this type of work were: positive interdependence, responsibility, and stimulating interaction were highlighted, and the need to strengthen social skills and group processing was identified. The relevance of investigating more about cooperative work techniques in the virtual and artistic environment for people with disabilities was identified.
Keywords: Cooperative work; theater; virtual education; special education; education